(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1996)
Notes the discovery of silver gilt `Pictish’ penannular brooch fragments in association with part of an iron sword blade and corroded iron material including part of a sickle blade. `The fibres associated with the brooch’ by Thea Gabra-Sanders (761–2) and `The organic remains associated with the sword and sickle’ by Amanda Clydesdale (762) conclude proceedings.